Role and Regulation of Poly-3-Hydroxybutyrate in Nitrogen Fixation in Azorhizobium caulinodans - Nick Crang; Khushboo Borah; Euan K. James; Beatriz Jorrín; Patrick Green; Andrzej Tkacz; Alison K. East; Philip S. Poole (Molecular Plant-Microbe Interactions, 2021)
An Azorhizobium caulinodans phaC mutant (OPS0865) unable to make poly-3-hydroxybutyrate (PHB), grows poorly on many carbon sources and cannot fix nitrogen in laboratory culture. However, when inoculated onto its host plant, Sesbania rostrata, the phaC mutant consistently fixed nitrogen. Upon reisolation from S. rostrata root nodules, a suppressor strain (OPS0921) was isolated that has significantly improved growth on a variety of carbon sources and also fixes nitrogen in laboratory culture. The suppressor retains the original mutation and is unable to synthesize PHB. Genome sequencing revealed a suppressor transition mutation, G to A (position 357,354), 13 bases upstream of the ATG start codon of phaR in its putative ribosome binding site (RBS). PhaR is the global regulator of PHB synthesis but also has other roles in regulation within the cell. In comparison with the wild type, translation from the phaR native RBS is increased approximately sixfold in the phaC mutant background, suggesting that the level of PhaR is controlled by PHB. Translation from the phaR mutated RBS (RBS*) of the suppressor mutant strain (OPS0921) is locked at a low basal rate and unaffected by the phaC mutation, suggesting that RBS* renders the level of PhaR insensitive to regulation by PHB. In the original phaC mutant (OPS0865), the lack of nitrogen fixation and poor growth on many carbon sources is likely to be due to increased levels of PhaR causing dysregulation of its complex regulon, because PHB formation, per se, is not required for effective nitrogen fixation in A. caulinodans.[Graphic: see text] Copyright © 2021 The Author(s). This is an open access article distributed under the CC BY 4.0 International license.